(untitled) (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines leadership. We present insights from a highly influential paper. Here are the highlights from this paper: This study aims to examine the effect of transformational leadership on employee voice behavior. Specifically, this study investigates the mediating role of positive affect in linking transformational leadership with voice and the moderating role of over-qualification in influencing the mediation of positive affect. In particular, a two-wave survey was conducted. A sample of 271 participants complete a questionnaire measuring transformational leadership, positive affect and various demographic variables in the first wave. Then, they complete a second questionnaire measuring perceived overqualification and voice behavior 2 weeks later. We conduct a series of multiple regression analyses to test the model. The results show that positive affect partially mediated the relationship between transformational leadership and employee voice behavior. Over-qualification moderated the relationship between positive affect and voice. In addition, moderated mediation analyses reveal that positive affect mediates the relationship between transformational leadership and voice only for highly overqualified employees. This study investigates a new method linking transformational leadership and voice from an affective perspective by finding the mediating effect of positive affect. We also verify the role of “energized to” process in shaping proactive behaviors. Finally, this study examines the boundary conditions of the effect of positive affect on voice. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.